Factors That Affect Savings In Islamic Banking - Putri Cahya Rosyadah; Nur Rachmat Arifin; Ridan Muhtadi; Mohamad Safik (Universitas Islam Negeri (UIN) Walisongo Semarang, 2020)
AbstractPurpose - The purpose of this study is to examine the effect of macroeconomic variables on the amount of savings in Islamic banks in Indonesia.Method - This study use quantitative research type using secondary data using OLS (ordinary least square) analysis which aims to examine the independent variable on the dependent variable.Result - The results of this study indicate that inflation and exchange rate variables do not affect the amount of savings, M2 variable has a positive and significant effect on the amount of savings. While the SBI variable has a negative and significant effect on the amount of savings.Implication - This study uses the data from Central bank of IndonesiaOriginality - This study uses several macroeconomic variables that are used to test its effect on the amount of savings in Islamic banking. By using secondary data taken from official government institutions for several years. The results show that macroeconomic variables greatly affect the customer's decision to save in Islamic banking.